2022
DOI: 10.3390/nu14142936
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cheese Intake on Cardiovascular Diseases and Cardiovascular Biomarkers

Abstract: Background: A growing number of cohort studies revealed an inverse association between cheese intake and cardiovascular diseases, yet the causal relationship is unclear. Objective: To assess the causal relationship between cheese intake, and cardiovascular diseases and cardiovascular biomarkers. Methods: A two-sample Mendelian randomization (MR) analysis based on publicly available genome-wide association studies was employed to infer the causal relationship. The effect estimates were calculated using the rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…The poultry intake frequency of 2-4 times per week was the most healthy frequency compared to the other frequencies of eating poultry, having a lower risk of CAD (OR=0.235, CI=[0.202, 0.272]) compared with never eating poultry. These three lifestyles were also proven to reduce the risk of CAD in previous studies (walking pace [33]; cheese intake [34]; and poultry intake [35]). Besides, the tobacco smoking on most or all day significantly increased the risk of CAD compared with no tobacco smoking in the present, and the other lifestyles had weak impacts on the disease risk ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The poultry intake frequency of 2-4 times per week was the most healthy frequency compared to the other frequencies of eating poultry, having a lower risk of CAD (OR=0.235, CI=[0.202, 0.272]) compared with never eating poultry. These three lifestyles were also proven to reduce the risk of CAD in previous studies (walking pace [33]; cheese intake [34]; and poultry intake [35]). Besides, the tobacco smoking on most or all day significantly increased the risk of CAD compared with no tobacco smoking in the present, and the other lifestyles had weak impacts on the disease risk ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although cheese is a full-fat dairy product that may be intuitively linked to increased risk of PAD and abdominal AA due to its high saturated fatty acid content and effect on blood cholesterol levels [24][25][26], a study by Ageno et al failed to demonstrate LDL-cholesterol as a risk factor for DVT and PE [27]. Moreover, a MR analysis indicated that cheese intake was inversely associated with PAD, with no observed associations for PE [10]. It is worth noting that evaluating the effect of cheese on PVDs based solely on saturated fatty acids may be inadequate, as the impact of food on a single biomarker such as blood cholesterol may not fully capture the risk of PVDs.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review demonstrated that moderate cheese intake (50 g/day) was associated with a lower cardiovascular disease risk, while a multinational prospective cohort study found that cheese intake was linked to a lower risk of mortality and major cardiovascular events [9]. Additionally, a Mendelian randomization (MR) analysis found that cheese intake was inversely associated with peripheral artery disease (PAD), with no observed associations for pulmonary embolism (PE) [10]. Nevertheless, given that PAD is an atherosclerotic occlusive disease, some studies suggested that cheese intake may have a positive association with atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although cheese was a full-fat dairy product that may be intuitively linked to increased risk of PAD and abdominal aortic aneurysm due to its high saturated fatty acid content and effect on blood cholesterol levels [20][21][22], a study by Ageno et al failed to demonstrate LDL-cholesterol as a risk factor for DVT and PE [23]. Moreover, a mendelian randomization analysis indicated that cheese intake was inversely associated with PAD, with no observed associations for PE [10]. It is worth noting that evaluating the effect of cheese on PVDs based solely on saturated fatty acids may be inadequate, as the impact of food on a single biomarker such as blood cholesterol may not fully capture the risk of PVDs.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review demonstrated that moderate cheese intake (50 g/day) was associated with a lower cardiovascular disease risk, while a multinational prospective cohort study found that cheese intake was linked to a lower risk of mortality and major cardiovascular events [9]. Additionally, a mendelian randomization analysis found that cheese intake was inversely associated with peripheral artery disease (PVD), with no observed associations for pulmonary embolism [10]. Nevertheless, given that PAD is an atherosclerotic occlusive disease, some studies suggested that cheese intake may have a positive association with atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%